3.7k views
2 votes

\frac{2 {x}^(3) + 4 {x}^(2) - 5 }{x + 3}
I need help with this one.​

User SeanJA
by
4.5k points

1 Answer

2 votes

2x³ = x2x², and

2x² (x + 3) = 2x³ + 6x²

Subtract this from the dividend to get a remainder of

(2x³ + 4x² - 5) - (2x³ + 6x²) = -2x² - 5

-2x² = x • (-2x), and

-2x (x + 3) = -2x² - 6x

Subtract this from the last remainder to get a new one of

(-2x² - 5) - (-2x² - 6x) = 6x - 5

6x = x6, and

6 (x + 3) = 6x + 18

This gives a new remainder of

(6x - 5) - (6x + 18) = -23

x does not divide -23, so we're done, leaving us with


(2x^3+4x^2-5)/(x+3)=2x^2-2x+6-(23)/(x+3)

User Oramas
by
5.1k points